Multivariate Analysis of the Relations Between Some Blood Biochemistry Parameters, Morphological Characters and Tonic Immobility in Broiler - AKKARTAL, ERKUT; MENDES, MEHMET; KURSUN, ILGIN (Asian Journal of Chemistry, 2010)
Multivariate multiple regression analysis (MMLR) and multidimensional scaling technique (MDS) were used to investigate relations between blood biochemistry parameters (white blood cells) and differences between two sides of some morphological characteristics (shank length, shank width, face width, face length) and tonic immobility. Sixty male birds were used in this study. According to the results of MMLR, the overall effect of basophil (P = 0.05), monocyte (P = 0.004) and eosinophil (P = 0.011) on dependent variables were statistically significant while the overall effect of lymphocyte (P = 0.630) and heterophil (P = 0.2937) were not statistically significant. Univariate F tests indicated that the shank width (P = 0.033) and face width (P = 0.047) were significantly related to the set of predictors, while shank length (P = 0.537), face length (P = 0.2344) and tonic immobility (P = 0.703) are not significantly related to the set of predictors. The MDS results showed that the differences between two sides of shank width were also related to Monocyte, Eosinophil and basophil while face length, face width and tonic immobility were related to lymphocyte and heterophil.